High-spatial resolution functional chemistry of nitrogen compounds in the observed UK meteorite fall Winchcombe - Vollmer, Christian; Kepaptsoglou, Demie; Leitner, Jan; Mosberg, Aleksander B.; El Hajraoui, Khalil; King, Ashley J.; Bays, Charlotte L.; Schofield, Paul F.; Araki, Tohru; Ramasse, Quentin (Nature Communications, 2024)
Organic matter in extraterrestrial samples is a complex material that might have played an important role in the delivery of prebiotic molecules to the early Earth. We report here on the identification of nitrogen-containing compounds such as amino acids and N-heterocycles within the recent observed meteorite fall Winchcombe by high-spatial resolution spectroscopy techniques. Although nitrogen contents of Winchcombe organic matter are low (N/C ~ 1-3%), we were able to detect the presence of these compounds using a low-noise direct electron detector. These biologically relevant molecules have therefore been tentatively found within a fresh, minimally processed meteorite sample by high spatial resolution techniques conserving the overall petrographic context. Carbon functional chemistry investigations show that sizes of aromatic domains are small and that abundances of carboxylic functional groups are low. Our observations demonstrate that Winchcombe represents an important addition to the collection of carbonaceous chondrites and still preserves pristine extraterrestrial organic matter.
Gesehen am 03.06.2025